Somewhat Opinionated A New York dance journal - Barnes, Clive 1927-2008 (Dance Books Ltd., Alton,Hampshire (UK), 2008)
Blooklyn Academy of Music 27 February-2 March. New York City Center 4-23 March. New York City Center 1-20 April. New York City Center 29 April-11 May. PALABRAS CLAVE: Nina Ananashvili, State Ballet of Georgia, Paul Taylor Dance Company, Kirov Ballet - Mariinski, William Forsythe, company's Jerome Robbins Celebration.